2014
DOI: 10.1142/s0219091514500179
|View full text |Cite
|
Sign up to set email alerts
|

Fear Sentiment, Liquidity, and Trading Behavior: Evidence from the Index ETF Market

Abstract: This paper explores how the fearful market-based sentiment indicators affect investor trading behavior and market liquidity. Our results show that a high degree of fearful market-based sentiment induces more sell orders along with a reduction in market liquidity, and vice versa. In addition, most of our findings suggest that the fear sentiment, in the case of extremely high implied volatility, decreases net buying volume more significantly. As for the interaction between fearful market-based sentiment and inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Therefore, increased political uncertainty causes investors to be pessimistic about the future prospect of their investments, subsequently leading to a reduction in trading activity and liquidity (Debata and Mahakud 2018). Studies by Chiu et al (2014) and Tseng and Lee (2016) have found that investor sentiment plays a particularly important role in the liquidity of ETFs.…”
Section: Kylementioning
confidence: 99%
“…Therefore, increased political uncertainty causes investors to be pessimistic about the future prospect of their investments, subsequently leading to a reduction in trading activity and liquidity (Debata and Mahakud 2018). Studies by Chiu et al (2014) and Tseng and Lee (2016) have found that investor sentiment plays a particularly important role in the liquidity of ETFs.…”
Section: Kylementioning
confidence: 99%
“…The notion of rationality in asset pricing and assumptions under the Capital Asset Pricing Model (CAPM) are frequently challenged, and Hirshleifer (2001) provides a comprehensive survey of the literature. Market scenarios may influence the association of expectations and returns, as reported in Chiu et al (2014), who use index and financial exchange-traded funds (ETFs) to find an asymmetric effect on equity liquidity and investor trading behavior during the subprime crisis period. Kumar and Lee (2006) examine whether the buy-sell activities of retail investors contain a common directional component.…”
Section: Relevant Literaturementioning
confidence: 99%